Response of Late Valencia Sweet Orange (Citrus sinensi (L.) Osbeck) to fertilization in the semi-deciduous forest agro-ecological zone of Ghana - Akosah, D.K.; Adjei-Nsiah, S.; Brentu, F.C. (University of Ghana, 2020)
We conducted a study to determine the response of Late Valencia sweet orange to organic and inorganic fertilizer application for two seasons in the semi-deciduous forest agro-ecological zone of Ghana. The experiment which was conducted in a randomized complete block design with four replications consisted of six treatments: 9 t/ha oil palm empty fruit bunches (EFB); 4t/ha Poultry manure (PM); NPKZn (90kg/ha N, 60kg/ha P, 80kg/ha K and 4.8kg/ha Zn); 4.5 t/ha EFB+NPKZn (45kg/ha N, 30kg/ha P, 40kg/ha K and 2.40kg/ha Zn); 2t/ha PM + NPKZn) (45kg/ha N, 30kg/ha P, 40kg/ha K and 2.40kg/ha Zn) and Control. In the 2019 harvest season, the treatment PM+NPKZn recorded the highest yield of 14.71t/ha while the control recorded the least yield (6.37t/ha). In the 2020 harvest season, fruit yield ranged from 17.3 t/ha with the NPKZn treated plots 28.8t/ha with the EFB treated plots to. Economic analysis shows that for the five fertilizer application treatments, the highest benefit/cost ratio was attained with the EFB treatment for the two harvesting seasons combined. Fertilization did not significantly affect leaf nutrient content 253 days after application. However, leaf N and K contents were generally higher 253 days after fertilizer application than the initial levels while P level did not change. Soil analysis 253 days after nutrient application showed an increase in total N, OC and available P while pH level decreased. The study suggests the need for farmers to adopt the use of crop residues for maintaining soil fertility of citrus orchards for improved fruit production.
Seminar
Keywords: soil fertility; agro-ecological zone; Ghana; fertilizer